Street as the place for conviviality?: relationships between people, products, and place in Cape Town CBD - Nakamura, Matsuri (Social Anthropology, 2025)
This ethnographic study explores the dynamics of encounter and interaction within a shared urban space, focusing on St. George's Mall in Cape Town Central Business District. This vibrant street, lined with stalls operated by migrants and a few South African traders, is a nexus of diverse flows—locals, migrants, and tourists—all circulating within a space of ‘multiple and unforeseen encounters'. Drawing insights primarily from street vendors, who have become ‘street-wise' through their long-term presence and interactions, the study examines how relationships are forged and negotiated within this fluid environment. These vendors form close-knit bonds with neighbouring vendors and those working around them, creating a “family” that transcends traditional boundaries of gender, religion, race, and nationality. This mutual support system, encompassing both business and personal life, is vital for their survival and success. However, this ‘family-like' relationship is not utopian. Tensions exist due to business competition and interpersonal conflicts, necessitating ongoing negotiation, sharing responsibilities, and respecting established norms. Despite these challenges, the vendors' interdependence fosters a sense of “being together” amidst difference and disagreement, highlighting the complexities of convivial urban relationships. The study also examines the constant circulation of people and goods that characterises St. George's Mall. This fluidity underscores the street's open-ended structure and intrinsic connections to the surrounding urban environment and transnational networks. The vendors, amidst this mobility, forge connections and develop a contingent sense of belonging to the space—a belonging that is fluid, pluralistic, and living with difference and tension. St. George's Mall thus emerges as a metaphor for open-ended belonging in the face of mobility and difference. It challenges the narratives of exclusion and xenophobia prevalent in South Africa, reimagining ‘others' as individuals with names and faces. By examining the encounters, mobility, and circulations on St. George's Mall, this study explores the extent to which this urban space fosters convivial relationships, offering a glimpse into the possibilities for ‘fulfilment-seeking incompleteness' in the city.